Poverty impacts of food price increases in Burkina Faso - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
The prices of many agricultural commodities, including many staple grains, started to increase in mid-2020 partly due to supply chain bottlenecks associated with the outbreak of Covid-19. The invasion of Ukraine by Russia in February 2022 caused an additional spike in commodity prices, particularly wheat and maize. This brief estimates the impact of these price increases on poverty in Burkina Faso. It is part of a series of six such briefs that estimate the poverty impact of higher world prices for staple grains. The other briefs cover Kenya, Ethiopia, Niger, Nigeria, and Mali (see Minot and Martin, 2023a and 2023b; Martin and Minot, 2023a, 2023b, and 2023c). We use the same approach in all six country studies. The analysis starts by exploring the effect of the rise in international grain prices on the real price of selected grains in the domestic markets of the country. Next, we estimate the impact of the changes in domestic grain prices on the real income of each household in a nationally representative survey, taking into account the importance of the commodities in consumption and as a source of income for each household. Finally, changes in headcount poverty (the share of people living below the poverty line) are estimated based on the changes in real income for each household in the sample. We focus on the prices of maize, wheat, and sorghum for reasons discussed below. The methods are described in more detail in a method brief.